Characterization of an Aplysia vasotocin signaling system and actions of posttranslational modifications and individual residues of the ligand on receptor activity - Xu, Ju-Ping; Ding, Xue-Ying; Guo, Shi-Qi; Wang, Hui-Ying; Liu, Wei-Jia; Jiang, Hui-Min; Li, Ya-Dong; Fu, Ping; Chen, Ping; Mei, Yu-Shuo; Zhang, Guo; Zhou, Hai-Bo; et al. (Frontiers in Pharmacology, 2023)
Vasopressin/oxytocin signaling system is present in both protostomes and deuterostomes, and plays various physiological roles. Although there were reports for both vasopressin-like peptides and receptors in mollusc Lymnaea and Octopus, no precursor or receptors have been described in mollusc Aplysia. Here, through bioinformatics, molecular and cellular biology, we identified both the precursor and two receptors for Aplysia vasopressin-like peptide, which we named as Aplysia vasotocin (apVT). The precursor provides evidence for the exact sequence of apVT, which is identical to conopressin G from cone snail venom, and contains 9 amino acids, with two cysteines at position 1 and 6, similar to nearly all vasopressin-like peptides. Through inositol monophosphate (IP1) accumulation assay, we demonstrated that two of three putative receptors we cloned from Aplysia cDNA are true receptors for apVT. We named the two receptors as apVTR1 and apVTR2. We then determined the roles of post-translational modifications (PTMs) of apVT, i.e., the disulfide bond between two cysteines and the C-terminal amidation on receptor activity. Both the disulfide bond and amidation were critical for activation of the two receptors. Cross-activity with conopressin S, annetocin from an annelid and vertebrate oxytocin showed that although all three ligands can activate both receptors, the potency of these peptides differed depending on their residue variations from apVT. We therefore tested the roles of each residue through alanine substitution, and found that each substitution could reduce the potency of the peptide analog, and substitution of the residues within the disulfide bond tended to have a larger impact on receptor activity than substitution of those outside the bridge. Moreover, the two receptors had different sensitivity to the PTMs and to single residue substitution. Thus, we have characterized the Aplysia vasotocin signaling system and showed how the PTMs and individual residues in the ligand contributed to receptor activity.